ANALYSIS OF THE USE OF HUMAN CAPITAL IN THE FIELD OF SERVICES IN THE REPUBLIC OF KARAKALPAGISTAN - Dauletmuratov Adilbay Mirzabaevich (Scholar Express Journals, 2024)
The economy of Germany, an economically highly developed country in the West, is based on services and science, and services in the economy account for more than 78.0 percent, and services directly related to industrial production account for more than 40.0 percent. . As a conclusion, it can be said that the more efficient the economy is, the more the demand for science and services will increase.
Keywords: Economically; highly developed